The Proximity between Hallucination and Delusion Dimensions: An Observational, Analytic, Cross-Sectional, Multicentre Study - Telles-Correia, Diogo; Moreira, Ana L.; Gama Marques, João; Saraiva, Sérgio; Moreira, Cátia A.; Antunes, Filipa; Almeida, Carolina; Rocha, Nuno B. (Frontiers in Psychology, 2016)
5. In the current psychiatric classifications, hallucinations (mainly auditory hallucinations) are one of the fundamental criteria for establishing a schizophrenia diagnosis or any of the related psychotic disorder’s diagnoses. 6. Throughout the history of Psychiatry the conceptual proximity between delusions and hallucinations in the psychiatric patient was maintained until the end of the XIX century, with several supporters during the XX century. Their frontier was not yet definitely defined in terms of Descriptive Psychopathology, and much less so in terms of biochemical and anatomical models. 7. In this article we aimed to analyse the dimensions of both hallucinations and delusions in a sample of patients with schizophrenia and schizoaffective disorder. We also intend to find the determinants of the main dimensions of hallucinations. 8. One hundred patients with schizophrenia or schizoaffective disorder from both the outpatient and inpatient units of the Psychiatry Department of Hospital of Santa Maria and the Centro Hospitalar Psiquiátrico de Lisboa were assessed by means of the Psychotic Symptom Rating Scales (PSYRATS). 9. In this study we found an empirical based model, where the main dimensions of hallucinations are determined by the central dimensions of delusions. 10. Keywords: “Psyrats”, “Hallucinations”, “Psychopathology”, “Psychosis”, “delusions”